Extraction ،Purification and Characterization Of Peroxidase From cabbage (Brassica oleracea Var) - adnan Abbas, Ayat (Iraqi Journal of Science, 2023)
The activity of peroxidase (POD) in cabbage was evaluated usingspectrophotometric method. The enzyme was extracted from the cabbage leaveswith 0.1 M phosphate buffer solution pH 7. 0 . POD activity was determined using(O-dianisidine) as a substrate. The effects of the amounts of enzyme extract,substrate concentration, pH and temperature were investigated. The highest activityof POD was recored at 2 mg/ml. The highest activity of POD was optimized with16 mM O-dianisidine, The optimum pH was 7.0 for POD , The optimumtemperature was 30°C for POD. These optimum conditions were used todetermined the enzyme activities in cabbage sample. Acetone fractionatedperoxidase from crude extract of Brassica oleracea leaves (Cabbage) was purifiedon DEAE-Cellulose chromatographic columns. The specific activity of purifiedPOD is 103.70 (U/mg) ،which is 5.37 times more than the crude extract with28.72% recovery. Maximum pH, thermal activity and stability of this purifiedenzyme are also determined were 40°C